Genetic structure of Anisoptera costata in Southeast Vietnam - Lan Hong, Nguyen Phan; Minh Duc, Nguyen; Minh Tam, Nguyen (Vietnam Journal of Biotechnology, 2022)
Anisoptera costata is an endangered species in Vietnam, from habitat loss and over-exploitation. To protect this species, we analyzed 56 adult trees using eight microsatellites to investigate the genetic diversity within and among three A. costata populations, representing the range of distribution of this species in southeastern Vietnam. Our results showed low genetic diversity (NA = 2.5, HO = 0.244, HE = 0.268). Genetic population differentiation among populations was low (FST = 0.139), indicating high gene flow (Nm = 2.838). Genetic variation among individuals was 79.77%. These suggest a lack of genetic diversity in A. costata.  The clustering analysis also showed two genetic clusters. These results will provide necessary information to improve the efficiency of conservation and management of this species.